In the Red Zone - Jake Maddox (Stone Arch Books, 2020)
Star quarterback Alex has always played football with his best friend, Oscar. But when Oscar suddenly quits the team to join the school play, Alex feels blindsided and betrayed. Now pressure is mounting on and off the field. Can the two boys ever recover from their friendship fumble? Young readers will love the exciting football story and the electrifying full-color comic format in this Jake Maddox Graphic Novel.
Keywords: Sports Stories -- Sports Stories